2014
DOI: 10.1186/1477-7819-12-139
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guidance reduces pneumothorax rate and improves safety of thoracentesis in malignant pleural effusion: report on 445 consecutive patients with advanced cancer

Abstract: BackgroundMalignant pleural effusion (MPE) is an extremely common problem affecting cancer patients, and thoracentesis is an essential procedure in an attempt to delineate the etiology of the fluid collections and to relieve symptoms in affected patients. One of the most common complications of thoracentesis is pneumothorax, which has been reported to occur in 20% to 39% of thoracenteses, with 15% to 50% of patients with pneumothorax requiring tube thoracostomy.The present study was carried out to assess wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 25 publications
0
41
1
Order By: Relevance
“…Despite previous studies reporting the incidence of pneumothorax as high as 19%, recent studies have found pneumothorax to be uncommon following thoracentesis, with reported incidences ranging from 0% to 3% (6,9,19,20). A recent meta-analysis reported a summarized pneumothorax rate of 6.0%, which is comparatively higher than our result (5).…”
Section: Discussioncontrasting
confidence: 99%
“…Despite previous studies reporting the incidence of pneumothorax as high as 19%, recent studies have found pneumothorax to be uncommon following thoracentesis, with reported incidences ranging from 0% to 3% (6,9,19,20). A recent meta-analysis reported a summarized pneumothorax rate of 6.0%, which is comparatively higher than our result (5).…”
Section: Discussioncontrasting
confidence: 99%
“…Malignant pleural effusion (MPE) is an extremely common problem affecting cancer patients with advanced disease [1]. In metastatic gastric cancer, patients with pleural or lymphangitic metastasis have shorter survival with a 1.5- to 2-fold increased risk of death [2].…”
Section: Introductionmentioning
confidence: 99%
“…Large studies conducted in adults have shown how the routine use of LUS may drastically reduce (i.e., from 8.8% to 0.97%, P<0.0001) the risk of pneumothorax in thoracentesis (15). LUS may be used also to monitor the occurrence of pneumothorax after drainage removal, avoiding the repetition of chest X-RAY examinations (that is a routine practice in many Centers) (6,15). Utility of LUS has been proved also for tracheal tube verification in NICU (14).…”
mentioning
confidence: 99%
“…Our group (5) recently described a new potential application of chest ultrasound in the diagnosis of retrosternal clots after pediatric cardiac surgery, that are common cause of hemodynamic unbalance and often difficult to diagnosis with conventional echocardiography. LUS may also guide interventional procedures such as drainage insertion for pleural effusion and pneumothorax (8,15). Large studies conducted in adults have shown how the routine use of LUS may drastically reduce (i.e., from 8.8% to 0.97%, P<0.0001) the risk of pneumothorax in thoracentesis (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation